Parents' Weekend panel discussion about the University College (now Tisch College) in the Rabb room of the Lincoln Filene Center. Photo 121 - Sobecki, Nicki (Tufts Archival Research Center, 2008)
Parents' Weekend panel discussion about the University College (now Tisch College) in the Rabb room of the Lincoln Filene Center.